Beneficial Effects of New Zealand Blackcurrant Extract on Maximal Sprint Speed during the Loughborough Intermittent Shuttle Test - Mark ET Willems; Luke Cousins; David Williams; Sam D. Blacker (Sports, 2016)
New Zealand blackcurrant (NZBC) extract has been shown to enhance high-intensity intermittent treadmill running. We examined the effects of NZBC extract during the Loughborough Intermittent Shuttle Test (LIST) which involves 5 × 15 min blocks with intermittent 15-m maximal sprints, interspersed by moderate and high-intensity running to simulate team sport activity, and a subsequent run to exhaustion. Thirteen males (age: 22 ± 1 year, V ˙ O 2 max : 50 ± 5 mL·kg−1·min−1) participated in three indoor sessions (T: 24 ± 3 °C, humidity: 52% ± 9%). In the first session, a multistage fitness test was completed to determine peak running speed and estimate V ˙ O 2 max . Participants consumed NZBC extract in capsules (300 mg·day−1 CurraNZ™) or placebo (PL) (300 mg·day−1 microcrystalline cellulose M102) for seven days in a double-blind, randomized, cross-over design (wash-out at least seven days). NZBC extract did not affect average 15-m sprint times in each block. NZBC reduced slowing of the fastest sprint between block 1 and 5 (PL: 0.12 ± 0.07 s; NZBC: 0.06 ± 0.12 s; p < 0.05). NZBC extract had no effect on heart rate, vertical jump power, lactate and time to exhaustion (PL: 13.44 ± 8.09 min, NZBC: 15.78 ± 9.40 min, p > 0.05). However, eight participants had higher running times to exhaustion when consuming NZBC extract. New Zealand blackcurrant extract may enhance performance in team sports with repeated maximal sprints.